Book Review : INTERCULTURAL LANGUAGE TEACHING AND LEARNING - Kaswan Kaswan (STKIP Siliwangi, 2013)
The analysis of language and culture has been long and widely made. To mention a few, Lies Sercu (2005) addresses this issue in Foreign Language Teachers and Intercultural Competence, Soler and Jordan (ed, 2007) in Intercultural language Use and Language Learning, Nieto (2010) in Language, Cultural and Teaching, and Deardorff (2009) in The Sage Handbook of Intercultural Competence . Nevertheless, most recently this topic has received more attention and become more important, as discussed by Dasep Suprijadi and Euis Rina Mulyani in their research based articles. If the goal of language instruction is communicative competence, language instruction must be integrated with cultural and cross-cultural instruction for sociocultural competence is part of communicative competence, besides linguistic competence, discourse competence, formulaic competence, and interactional competence, as proposed by Celce-Murcia (1995) in Soler and Jorda (2007). Sociocultural competence refers to the speaker’s pragmatic knowledge, i.e. how to express messages appropriately within the overall social and cultural context of communication. This includes knowledge of language variation with reference to sociocultural norms of the target language. In fact a social or cultural blunder can be far more serious than a linguistic error when one is engaged in oral communication.